MENELISIK TAFSIR MODERASI BERAGAMA DALAM KALIGRAFI AYAT AL-QUR’AN DI MASJID KOTA PANGKALPINANG - Purwanto, Tinggal; Wahyudi, Wahyudi (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
This study seeks to interpret the calligraphy of Qur'anic verses in the Pangkalpinang City Mosque from the perspective of religious moderation. This study began by describing the calligraphy of the Qur'an installed on the wall of the Pangkalpinang City mosque. In the second stage, this study will interpret the calligraphy of Qur'anic verses with an interpretation approach. The results of this study show that the calligraphy of Qur'an verses, which is generally understood by the people of Pangkalpinang City as a decoration of the mosque wall to look aesthetic and have religious nuances, can ultimately become a medium to call for religious moderation, by balancing between the activities of this world and the hereafter through the selection of verses of the Qur'a